1999
DOI: 10.1247/csf.24.255
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of Extracellular Matrix Components in Expression of Matrix Metalloproteinases in Cultured Hepatic Stellate Cells.

Abstract: Hepatic stellate cells (HSCs) were changed in their morphology, proliferative activity, and functions by culturing on type I collagen gel, as compared to the culture on polystyrene surface. HSCs have been found to produce extracellular matrix components and matrix metalloproteinases (MMPs). In this study, we have assessed the effects of several types of substrata on the expression of MMPs in HSC culture. MMP-1 expression was detectable in HSC culture on polystyrene surface and on type I collagen gel by immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…MMP-2 mRNA was up-regulated in HSCs cultured on type I collagen gel, as compared with its level in the cells cultured on the polystyrene surface, type I collagen-coated surface, or Matrigel. However, even when HSCs were cultured in serum-supplemented DMEM, the active form of MMP-2 specifically appeared in HSCs cultured on type I collagen gel but not on a polystyrene surface, type I collagen-coated surface, and Matrigel (Li et al, 1999). Since the serum (FBS) used for cell culture contains a significant amount of pro-MMP-2 but no active form of MMP-2 (Li et al, 1999), as was shown in Fig.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…MMP-2 mRNA was up-regulated in HSCs cultured on type I collagen gel, as compared with its level in the cells cultured on the polystyrene surface, type I collagen-coated surface, or Matrigel. However, even when HSCs were cultured in serum-supplemented DMEM, the active form of MMP-2 specifically appeared in HSCs cultured on type I collagen gel but not on a polystyrene surface, type I collagen-coated surface, and Matrigel (Li et al, 1999). Since the serum (FBS) used for cell culture contains a significant amount of pro-MMP-2 but no active form of MMP-2 (Li et al, 1999), as was shown in Fig.…”
Section: Discussionmentioning
confidence: 89%
“…However, even when HSCs were cultured in serum-supplemented DMEM, the active form of MMP-2 specifically appeared in HSCs cultured on type I collagen gel but not on a polystyrene surface, type I collagen-coated surface, and Matrigel (Li et al, 1999). Since the serum (FBS) used for cell culture contains a significant amount of pro-MMP-2 but no active form of MMP-2 (Li et al, 1999), as was shown in Fig. 1, the pro-MMP-2 activation events are specific to the HSC culture on type I collagen gel, probably through up-regulation of MT1-MMP and TIMP-2.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…114 Active forms of MMP-1 and MMP-2 can be detected around human HSC cultured on collagen gel by in situ zymography and in the culture medium, respectively. 115 The expression of MMP-13 increases in rat liver MFB when the cells are embedded in attached collagen gel. However, the observed collagen degradation is a result of a joint action of a few proteinases.…”
mentioning
confidence: 96%